Dystrophin expression in an Egyptian family suffering from muscular dystrophy. Issue 1 (July 2016) - Achmawi, Ghada A.; Elsawy, Noha; El Assi, Hoda; Kassem, Heba Sh.; Talaat, Iman M.; El-Gendi, Saba M.
Abstract : Background: Immunohistochemical staining of dystrophin of muscle biopsies obtained from patients with muscular dystrophy helps in distinguishing the different clinicopathologic types quite accurately. Therefore, it is considered the gold standard in the diagnosis of multiple syndromes of muscle dystrophy. Objective: The aim of the present study was to clinicopathologically characterize an Egyptian family of a nonconsanguineous couple, with five (three males and two females) out of seven siblings affected with muscular dystrophy with varying degrees of severity. Materials and methods: Three affected siblings were subjected to biochemical and electrophysiological studies. The family pedigree was constructed to study the mode of inheritance. Histopathological examination and dystrophin immunohistochemical staining were performed on quadriceps muscle biopsy obtained from the three affected members. Results: The biochemical study of these patients showed a very high level of serum creatinine phosphokinase exceeding 1000 IU/l. The electrophysiological studies suggested myopathic changes. Histopathological examination of the muscle biopsies obtained confirmed the diagnosis of muscular dystrophy. The dystrophin immunohistochemical staining showed a heterogeneous pattern of protein expression, ranging from totally absent membranous staining in most fields in one sibling (the female patient), to weak and interrupted staining in the other two affected male siblings. Conclusion: Dystrophin immunohistochemical staining confirms the diagnosis of Duchenne muscle dystrophy/Becker muscle dystrophy dystrophinopathy by showing different patterns of dystrophin protein expression. Although Duchenne muscle dystrophy/Becker muscle dystrophy are both X linked, yet, in our study, the female sibling showed severe disease expression possibly because of skewed X inactivation.